Postoperative Stroke after Anterior Cervical Discectomy and Fusion: A Clinical Case Report - Cuong, Vu Van; The Hung, Dinh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 3, 2021)
Anterior cervical discectomy and fusion (ACDF) spine surgery has been performed extensively for the treatment of degenerative spine diseases with relatively low rates of complications. The reported incidence of postoperative cerebrovascular events associated with ACDF is only 0.13%, representing 1.51% of all complications. However, this complication is often highly disastrous and can lead to paralysis, and even death. In this study, a 42year-old male underwent anterior cervical discectomy and fusion (ACDF) at C34 and C45 levels through a right-sided approach. Three hours after the surgery, the patient suddenly developed left hemiplegia and facial palsy.. The patient was  treated with  aspirin and cerebromysin and fully recovered from motor and sensory deficits after 1 month. Keywords : Anterior cervical discectomy and fusion, postoperative stroke. References [1] P. S. Romano, D. R. Campa, J. A. Rainwater, Elective Cervical Discectomy in California: Postoperative in Hospital Complications And Their Risk Factors, Spine, Vol. 22, No. 1, 1997, pp. 2677-2692, https://doi.org/10.1097/00007632-199711150-00018. [2] B. S. Chozick, P. Watson, S. H. Greenblatt, Internal Carotid Artery Thrombosis After Cervical Corpectomy, Spine, Vol. 19, 1994, pp. 2230-2232, https://doi.org/10.1097/00007632-199410000-00020. [3] Y. C. Yeh, W. Z. Sun, C. P. Lin et al., Prolonged Retraction on The Normal Common Carotid Artery Induced Lethal Stroke After Cervical Spine Surgery, Spine, Vol. 29, No. 3, 2004, pp. 431-434, https://doi.org/10.1097/01.brs.0000141177.95850.b1. [4] J. E. Loret, P. Francois, C. Papagiannaki, Internal Sarotid Artery Dissection After Anterior Cervical Disc Replacement: First Case Report And Literature Review of Vascular Complications of The Approach, Eur J Orthop Surg Traumatol, Vol. 23, No. 1, 2013, pp. 107-110, https://doi.org/10.1007/s00590-013-1228-8. [5] M. Radhakrishnan, S. Bansal, G. S. Srihari, Perioperative Stroke Following Anterior Cervical Discectomy, Br J Neurosurg, Vol. 24, No. 1, 2010, pp. 592-594, https://doi.org/10.3109/02688691003711575. [6] Q. D. Yue, Carotid Artery Related Perioperative Stroke Following Anterior Cervical Spine Surgery: A Series of 3 Cases and Literature Review, Journal of Stroke And Cerebrovascular Diseases, Vol. 28, No. 2, 2019, pp. 458-463, https://doi.org/10.1016/j.jstrokecerebrovasdis.2018.10.024. [7] E. Matthew, Changes in Carotid Artery Blood Flow During Anterior Cervical Spine Surgery, Spine, Vol. 27, No. 2, 2002, pp. 152-155, https://doi.org/10.1177/2192568216688192. [8] D. C. Brooks, J. L. Schindler, Perioperative Stroke: Risk Assessment, Prevention and Treatment, Curr Treat Options Cardiovasc, Meds, Vol. 16, No. 1, 2014, pp. 282, https://doi.org/10.1007/s11936-013-0282-1. [9] E. C. Jauch, J. L. Saver, J. Adams, Guidelines for The Early Management of Patients with Acute Ischemic Stroke: A Guideline for Healthcare Professionals from The American Heart Association, American Stroke Association, Vol. 44, No. 1, 2013, pp. 870-947, https://doi.org/10.1161/STR.0b013e318284056a. [10] J. M. Cuellar, A. Petrizzo, R. Vaswani, Does Aspirin Administration Increase Perioperative Morbidity in Patients With Cardiac Stents Undergoing Spinal Surgery, Spine, Vol. 44, No. 1, 2015, pp. 629-635, https://doi.org/10.1097/BRS.0000000000000695.